ACCOUNTING PRACTICE MODEL ON THE HOME INDUSTRY UD. AGUNG - Benny Afianto; Rosnawintang Rosnawintang; La Ode Anto (Mega Aktiva, 2019)
In the final stage, an accounting practice will produce information that is beneficial to the company, researchers have revealed the findings of his research regarding the existence of accounting practices in the home industry of UD. Agung. Based on an explanation of the philosophical assumptions that underlie the research methodology, philosophically this research is placed in a position as a research with an interpretive paradigm. This study is not intended to provide generalizations on accounting models in other home industries. The results of this study state that for accounting records UD. Agung is carried out very simply, only records incoming/outgoing money, incoming/outgoing goods and paying the craftsmen's wages. From the simple recording, found the values of sincerity, trust and honesty, and justice are the values that underlie accounting practices in the home industry of UD. Agung. Besides that, the existence of intensity of accounting practices is still very low and its application is still very simple. The meaning of accounting for human resources can be seen when the informant determines production costs and selling prices. For salary management, it can be recognized as an investment in human resource accounting in the compensation model group. Accounting practices at UD. Agung is not only interpreted as an attempt to calculate the numbers then presented in the form of notes. However, accounting in this study is also interpreted as an attempt to calculate the numbers carried out in the minds and minds of business people without holding records.